Time Series Model Analysis Using Autocorrelation Function (ACF) and Partial Autocorrelation Function (PACF) for E-wallet Transactions during a Pandemic - Yakubu, Usman Abbas; Saputra, Moch Panji Agung (iora, 2022)
The use of e-wallet can be accessed easily via the internet, this can create a positive impact for economic stability after the Covid-19 pandemic. This can move the wheels of the community's economy, through online shopping and the use of e-wallet among the public. The use of a number of digital services in Indonesia has increased during the Covid-19 pandemic. The first position is occupied by e-commerce and the second position is occupied by digital wallets which increased by 65%. Based on data from the increasing number of e-wallet service users in Indonesia. There are several forms of e-wallet that have a large scale, such as GoPay, OVO, Tokopedia, and Bukalapak. Several types of e-wallets can be analyzed for time series models, so that they can help project e-wallet transactions in the post-pandemic future. The method for obtaining the time series model is using the Autocorrelation Function (ACF) and the Patial Autocorrelation Function (PACF).